ضوابط اعتبار المقاصد عند الإمام الشاطبي - قاسم محمد الصغير; أ.د. شطة مصطفى (جامعة عمار ثليجي الاغواط, 2023)
لا شك أن للمقاصد دور كبير في مجال الاجتهاد خاصة وفي سائر المجالات عامة وقد تبوّأت في عصرنا الحالي مكانة مهمّة من خلال البحوث والدراسات وعقد المؤتمرات حولها . ولهذا كان بحثي منصبًّا حول الضوابط التي اعتبرها الإمام الشاطبي في مقاصد الشريعة في كتابه الموافقات تحديدًا لما له من السبق في التأسيس لعلم المقاصد والفضل في إرساء قواعده ، فكان لزامًا من توضيح هذه الضوابط التي هي معيار لاختبار مقاصدية الأحكام والمصالح و فهم النصوص على الوجه المناسب لمراد الشارع أولا واستنباط الأحكام وتنزيلها على الوجه الصحيح ثانيًا. ولإزالة اللُّبس الواقع حولها ، لئلا يعتبر من المقاصد ما ألغاها الشارع فيحصل بسببه الخطأ والزلل. There is no doubt that the purposes have a great role in the field of jurisprudence in particular and in other fields in general It has assumed an important position in our time through research, studies and conferences . That is why my research was focused on the rules that Imam shatibi considered in the purposes of Sharia in his book (al mouafakat) precisely ; because of his precedence in establishing the science of purposes and thanks to the establishment of its rules, it was necessary to clarify these rules, which are a criterion for testing the intent of provisions and interests and understanding the texts properly for what the street wants first and derive the provisions and download them correctly secondly. And to remove the confusion around it, so that it is not considered one of the purposes that the street canceled, and it happens because of the error and slip.